ELISA method to detect ABO blood group in external secretion fluids - Abdul Halim Sadikin; Yefta Moenadjat; Novi Sylvia Hardiany (Indonesian Society for Biochemistry and Molecular Biology, 2019)
Background: Usually it takes a large number of volume sample to determine blood group from external secretion fluids. But, in certain condition, samples are only available in very small amount. The objective of this study is to detect the presence of ABO blood group substances in mucosal fluid using ELISA technique, thus only requires small amount of samples. Objective: To develop an ELISA technique using the current anti-ABO antibodies for determination of blood group by hemagglutination technique and second peroxidase label antibody specific for mouse IgG, originally used for another ELISA technique. Methods: 100 μl of diluted human intestinal mucosal fluid were incubated overnight in 4oC in ELISA microplate wells, followed by addition anti-ABO antibodies. Then after incubation, a second revealing antibody anti mouse IgG labeled with peroxidase was added. After a brief incubation, substrate H2O2 and chromogenic TMB were added. Results: Positive reaction is marked by development of blue colour, which, on termination enzymatic reaction by addition 100 μl H2SO4 change to yellow. Conclusion: An ELISA method for detecting ABO substance in mucosal fluid can be developed from antibodies not specifically made for this technique, but specific only for the target.